THE APPLICATION OF MAKE A MATCH LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN SCIENCE - Yuliana Yenita Mete; Ainun Jariyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Based on the observation, the problem found in Class IV at SDK Nangakeo was the low achievement in students’ learning outcomes due to the learning method used being more passive, which caused the learning atmosphere to become unconducive. To solve this problem, the teacher applied the Make a Match learning model. The aim is to find out the improvement of students’ learning outcomes in the science subject with the topic of plant leaf structure and its function at SDK Nangakeo, Ende Regency. The implementation process used the Classroom Action Research (CAR) model, which consists of four stages, namely planning, implementation, observation, and reflection. Data were collected through observation, interviews, and tests. Data analysis techniques used quantitative descriptive analysis. After analyzing, the results of the study showed that in Cycle I, the average score was 58.10 with a completeness percentage of 31.57%, and in Cycle II, the results increased to 84.94 with 100% completeness. Based on these results, it can be concluded that the application of the Make a Match learning model can improve students’ learning outcomes.